Personality, Challenges and Performance: Evidence from Ethiopia's Young Entrepreneurs. Issue 2 (June 2019) - Kar, Brajaballav; Ahmed, Yimer Ayalew
The debate on whether entrepreneurs are born or can be made is long-standing. However, every entrepreneur has a specific combination of personality traits which predisposes him or her to face various challenges posed in entrepreneurship. Second, such combination of traits and challenges is expected to produce differences in business performances. This article is an outcome of a PhD. research undertaken on youth entrepreneurship in Ethiopia. It reports various relationships among personality traits, perceived challenges, and business performances of youth entrepreneurs in Ethiopia. The questionnaire-based survey had a sample size of 350 young entrepreneurs. Personality traits included the need for achievement, need for independence, the locus of control and propensity for risk-taking; business challenge factors included finance, business development, training and education, marketing, administrative and legal, and socio-cultural elements. The analysis indicated that (a) the entrepreneurial personality factors are strongly correlated, (b) different challenges faced by entrepreneurs are strongly correlated, (c) personality factors significantly influence the perceived performance outcome and (d) higher level of performance is correlated with higher level of perceived challenges. The results are found to be statistically significant. The article discusses the policy implications and further research directions.